Penerapan Green Marketing pada Produk Bubble Wrap dalam Meningkatkan Purchase Intention dan Perceived Value - Kuswandi, Helen Atris Romadhona Kuswandi Putri; Wiraguna, Rayie Tariaranie (Politeknik Negeri Jember, 2024)
This study aims to determine the application of green marketing on OCUWRAP products and application of green marketing to increase purchase intention and perceived value. OCUWRAP is a biodegradable bubble wrap product made from cassava starch and dried sponge gourd. This research was conducted using an interview method with a descriptive qualitative approach. Data obtained from interviews conducted with marketing and development managers, cosmetic store owners, and consumers were processed using the triangulation method. This study found that green marketing implemented has increased purchase intention and perceived value of its products. The implementation of green marketing by OCUWRAP is carried out in various aspects, namely environmentally friendly products, premium prices and environmentally friendly marketing and distribution. The results of this study indicate that the green marketing strategy has increased purchase intention for the product. Green marketing that has been implemented can also increase the perceived value felt by OCUWRAP consumers.